"Phillips Curve" in selected ASEAN countries : new evidence from panel data analysis - Furuoka, Fumitaka *; Munir, Qaiser (Sunway University College, 2009)
This paper uses panel data analysis to analyse the relationship between the unemployment rate and the inflation rate in five ASEAN countries (i.e. Malaysia, Singapore, Indonesia, Thailand and the Philippines). Since the trade-off relationship between employment and wage inflation rate in the United Kingdom was pointed out by William Phillips in 1958, this hypothesis of the ?Phillips Curve? remains an important foundation for macroeconomics. The main findings from the panel data analysis are that there is no trade-off relationship between the unemployment rate and the inflation rate in these ASEAN countries